Leading through influence at scale : open source security at the linux foundation - Chesbrough, Henry William; Masko, John (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2022)
This case puts students in the shoes of Jim Zemlin, who serves as executive director of the Linux Foundation (LF), a non-profit charged with providing support for the open source software (OSS) development community. Zemlin has received a call from the deputy director of national intelligence, alerting him of a recently-discovered security flaw in an OSS product, called Apache Log4j. This is a widely used piece of software, making the flaw a vulnerability for businesses all over the world. Zemlin has been "invited" to an emergency meeting of technology leaders and national security leaders, to discuss how to respond to the threat. With no direct power over developers, what options are available to Zemlin? Which should he choose?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Technological innovations -- Case studies